Effectiveness of Bilateral Inferior Petrosal Sinuses Sampling in Tumor Lateralization: Intraoperative Findings and Postoperative Results - Harker, Pablo; Feo-Lee, Oscar; Giraldo-Grueso, Manuel; Puentes, Juan Carlos (Journal of Neurological Surgery Part B: Skull Base, 2017)
Object Diagnosis and treatment of Cushing's disease (CD) is a demanding endeavor. We evaluated the effectiveness of inferior petrosal sinus sampling (IPSS) in preoperative tumor lateralization and surgical outcomes.Methods Fifty-two consecutive patients with CD and normal magnetic resonance imaging (MRI) were enrolled between 2009 and 2015. Selective catheterization of petrosal sinuses for IPSS was performed. All patients underwent microsurgical dissection, and if a lesion was found, underwent lesion resection. Demographic, biochemical, and intraoperative findings were prospectively collected and reviewed 6 and 12 months postoperatively.Results Forty-five patients (86.4%) had clear lateralization while seven patients had bilateral elevation. Twenty-two patients (42%) were found to have a macroscopic lesion, defined as an abnormal tissue during microsurgical dissection, which was thus resected. No patient had a lesion larger than 4 mm. Eighty-one percent of patients had the lesion where IPSS had been predicted. Hemi-hypophysectomy was performed on twenty-eight patients based on IPSS findings, since no lesion was found. Eighty-six percent of patients with lesion resection had biochemical remission by 12 months. Biochemical remission was documented in 78 and 71% of patients who underwent hemi-hypophysectomy by 6 and 12 months, respectively.Conclusion With careful microsurgical dissection, a macroscopic lesion could be found in a significant number of patients with normal MRI. When no lesion was found, we recommend performing a hemi-hypophysectomy based on IPSS findings, since prediction accuracy was high and remission rates were significant.
Keywords: petrosal sinuses sampling; Cushing's disease; tumor lateralization